Strategi Pengurangan Angka Perkawinan Anak di Kabupaten Bondowoso - Sunarto, Imam; Rohim, Rohim; Munawaroh, Lalilatul (Majalah Ilmiah DIAN ILMU, 2023)
This research aims to describe the Bondowoso District Government'sstrategy for reducing the number of child marriages. There are several partiesinvolved in formulating this strategy, including government institutions andcivil society organizations. The theory used in this research is the approach tothe role of actors in the formulation of public policy. The research method usedis qualitative with the technique of determining informants using purposive.Data analysis using interactive models, namely data collection, datacondensation, data display, and conclusion drawing/verifying. The strategy toreduce the number of child marriages in Bondowoso Regency by the SocialService for Women's Empowerment, Child Protection and Family Planning(DINSOSP3AKB) takes two approaches, namely an approach to parents and anapproach to children which involves several actors, both government and nongovernment.